ONOMATOPOEIA USAGE IN "AO NO HAKO" MANGA - Ibrahim, Archi Maulana; Ali, Mohammad (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This study aims to describe the types of onomatopoeia based on the theory stated by Kindaichi (1989) and the meaning of onomatopoeia based on the theory stated by Ono (2016). The data source of this research is a manga titled "Ao no Hako" by Kōji Miura chapter 1. The method used in this research is qualitative method with descriptive analysis approach. The result of this research is the discovery of 27 data on the use of onomatopoeia which in terms of types, the most appearing type is giongo as much as 14 data, followed by giyougo 8 data, then gitaigo 4 data and the last is giseigo. Then in the meaning section that appears, there are meanings related to humans, namely 13 data Followed by 13 data related to objects.